Perbandingan efektifitas berkumur air garam konsentrasi 0.9% dengan topikal anestesi benzocaine 20% terhadap terjadinya gag reflex saat pencetakan rahang - Susiani Tarigan; Irene Anastasia Tampubolon; Stanley Lieasdy (Prima Journal of Oral and Dental Sciences, 2022)
Background: Orthodontics and prosthodontic treatment requiring impression againts the patients, the impression step always causes an obstacle for operator or dentist because there some patients which have vomiting sensation (gag reflex). Gag reflex can be discribe as a normal mechanism to prevent foreign bodies from entering the trachea, pharynx, or larynx. Gag reflex can be prevented with several ways, one of it is topical anesthetic benzocaine 20%. Aim: to compare the effectiveness of gargling salt water concentration of 0.9% with a topical anesthetic benzocaine 20% in reducing the levels of gag reflex, some studies show that 20% benzocaine can inhibit the nerve receptors that influence its happening gag reflex. Methods: This research is cross-sectional with pre test and post test design. The research was conducted on students of Faculty of dentistry in Prima Indonenesia Univeristy the number of samples obtained as many as 54 people. Data analysis using SPSS 17.0 by using chi square analysis test. Result: Topical anesthetic benzocaine 20% is more effective to reduce the level of gag refelx than gargling with brine solution concentration of 0.9%. Conclusion: Based on the result of statistics test that conducted, can be conluded this research showed that topical anesthetic benzocaine 20% is more effective than gargling with brine solution concentration of 0.9% to reduce the level of gag reflex.